Biallelic VPS35L pathogenic variants cause 3C/Ritscher-Schinzel-like syndrome through dysfunction of retriever complex. Issue 4 (11th November 2019) - Kato, Kohji; Oka, Yasuyoshi; Muramatsu, Hideki; Vasilev, Filipp F; Otomo, Takanobu; Oishi, Hisashi; Kawano, Yoshihiko; Kidokoro, Hiroyuki; Nakazawa, Yuka; Ogi, Tomoo; Takahashi, Yoshiyuki; Saitoh, Shinji
Abstract : Background: 3C/Ritscher-Schinzel syndrome is characterised by congenital cranio-cerebello-cardiac dysplasia, where CCDC22 and WASHC5 are accepted as the causative genes. In combination with the retromer or retriever complex, these genes play a role in endosomal membrane protein recycling. We aimed to identify the gene abnormality responsible for the pathogenicity in siblings with a 3C/Ritscher-Schinzel-like syndrome, displaying cranio-cerebello-cardiac dysplasia, coloboma, microphthalmia, chondrodysplasia punctata and complicated skeletal malformation. Methods: Exome sequencing was performed to identify pathogenic variants. Cellular biological analyses and generation of knockout mice were carried out to elucidate the gene function and pathophysiological significance of the identified variants. Results: We identified compound heterozygous pathogenic variants (c.1097dup; p.Cys366Trpfs*28 and c.2755G>A; p.Ala919Thr) in the VPS35L gene, which encodes a core protein of the retriever complex. The identified missense variant lacked the ability to form the retriever complex, and the frameshift variant induced non-sense-mediated mRNA decay, thereby confirming biallelic loss of function of VPS35L. In addition, VPS35L knockout cells showed decreased autophagic function in nutrient-rich and starvation conditions, as well as following treatment with Torin 1. We also generated Vps35l −/− mice and demonstrated that they were embryonic lethal at an early stage, between E7.5 and E10.5. Conclusions: Our results suggest that biallelic loss-of-function variants in VPS35L underlies 3C/Ritscher-Schinzel-like syndrome. Furthermore, VPS35L is necessary for autophagic function and essential for early embryonic development. The data presented here provide a new insight into the critical role of the retriever complex in fetal development.